STRATEGI PEMBELAJARAN BERDIFERENSIASI DALAM MENGATASI KETERLAMBATAN BELAJAR SISWA PADA MATA PELAJARAN PKN DI SD INPRES YOTEFA - Wati, Jeshica Audevila Chrisdiana; Hidayah, Hidayah; Mutaqin, Alim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe differentiated learning strategies in overcoming students’ learning delays in Civics (PKn) at SD Inpres Yotefa Papua. The background of this study is based on differences in students’ learning readiness, low participation, and difficulties in understanding abstract civic concepts. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects consisted of classroom teachers and students experiencing learning delays. The results showed that differentiated learning was implemented through mapping students’ readiness, simplifying content, varying learning processes, applying flexible grouping, using concrete media, and providing multiple learning product options. Based on observation results, approximately 75% of students showed increased participation in learning, while 70% demonstrated gradual improvement in understanding Civics concepts. In addition, around 65% of previously passive students became more confident in asking questions, answering, and engaging in group discussions.These strategies proved to help students understand the material more contextually and improve their self-confidence. Therefore, differentiated learning can be considered an effective, inclusive, and relevant approach to overcoming students’ learning delays in Civics at the elementary school level.